Metafungsi Bahasa pada Novel Laut Bercerita Karya Leila S Chudori - Anastasia Nurhakim; Mahpudoh Mahpudoh; Rina Andriani (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze the language metafunctions found in the narrative and dialogue of the novel Laut Bercerita by Leila S. Chudori using Halliday’s Systemic Functional Linguistics approach. The research employs a descriptive qualitative method to describe how language functions in constructing meaning within literary discourse. Data were collected through the listening and note-taking techniques applied to a transcript of 40 selected sentences representing three different narrative contexts in the novel. The data were analyzed based on Halliday’s three metafunctions of language, namely ideational, interpersonal, and textual metafunctions. The findings reveal that the ideational metafunction is dominated by mental and relational processes, indicating the characters’ thoughts, emotions, experiences, and relationships with their social environment. The interpersonal metafunction is primarily realized through declarative clauses used to provide information, express viewpoints, and establish interactions between characters. Meanwhile, the textual metafunction demonstrates the organization of themes and rhemes that create coherence and facilitate the flow of information throughout the narrative. The novelty of this study lies in its application of Halliday’s metafunction analysis to Laut Bercerita, offering a deeper understanding of meaning construction and linguistic representation in contemporary Indonesian literary works.